Adsorption force of fibronectin controls transmission of cell traction force and subsequent stem cell fate. (April 2018) - Lin, Manping; Mao, Shilong; Wang, Jinfeng; Xing, Juan; Wang, Yuanliang; Cai, Kaiyong; Luo, Yanfeng
Abstract: The transmission of cell traction force (CTF) to underlying biomaterials is essential for adhered cells to measure and respond to their mechanical microenvironment. Given that the protein layer adsorbed on materials lies between the cells and materials, we hypothesize that the interfacial strength of protein-material interfaces (i.e., the adsorption force of proteins, F ad ) should have an important role in regulating the transmission of CTF. To test this hypothesis, rat mesenchymal stem cells (rMSCs) were cultured on poly(dimethyl siloxane) (PDMS) substrates with different F ad of fibronectin (FN), and the transmission of CTF was observed by immunofluorescence staining of FN and deformation of PDMS. As revealed, FN on substrates with low F ad is more liable to be desorbed by CTF, which prevents the transmission of CTF to substrates. In contrast, high F ad facilitates the transmission of CTF from rMSCs to the FN layer and PDMS substrates so that rMSCs can perceive the mechanical properties of substrates. We further demonstrated that the divergent transmission of CTF on low and high F ad substrates regulates the lineage specifications of rMSCs. Our study confirms the important role of F ad in CTF transmission and provides a new perspective to gain insights into cell-material interactions and cell fates, which may help to guide the design of better biomaterials. Graphical abstract: Highlights: A platform that regulates F ad on stiff and soft PDMS substrates is established by chemical modification of substrates. Low F ad prevents while high F ad facilitates the transmission of CTF from cells to PDMS substrates. rMSCs on low F ad substrates cannot but those on high F ad substrates can perceive the mechanical properties of substrates. The divergent transmission of CTF can regulate the differentiation of rMSCs.